2022
DOI: 10.1371/journal.pgen.1010282
|View full text |Cite
|
Sign up to set email alerts
|

Aging and sperm signals alter DNA break formation and repair in the C. elegans germline

Abstract: Female reproductive aging is associated with decreased oocyte quality and fertility. The nematode Caenorhabditis elegans is a powerful system for understanding the biology of aging and exhibits age-related reproductive defects that are analogous to those observed in many mammals, including dysregulation of DNA repair. C. elegans germline function is influenced simultaneously by both reproductive aging and signals triggered by limited supplies of sperm, which are depleted over chronological time. To delineate t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…The association between chromosomal aberrations and spontaneous abortions and pathologies have also been observed in domesticated mammals like equines (Shilton et al, 2020), bovines (Schmutz et al, 1996), and in mouse models (Williams et al, 2008). Studies on humans (Taylor et al, 2014;Thomas et al, 2021;Webster & Schuh, 2017), other mammals (Rizzo et al, 2019), and even the model nematode Caenorhabditis elegans (Toraason et al, 2022) have demonstrated that variables relating to the maternal germline, and in particular oocyte age, may increase the probability of nondisjunction during meiosis. The current evidence, while mostly limited to humans and domesticated mammals, suggests that chromosomal aberrations and their impacts on tness may be prevalent across taxa, and may be predisposed by genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 94%
“…The association between chromosomal aberrations and spontaneous abortions and pathologies have also been observed in domesticated mammals like equines (Shilton et al, 2020), bovines (Schmutz et al, 1996), and in mouse models (Williams et al, 2008). Studies on humans (Taylor et al, 2014;Thomas et al, 2021;Webster & Schuh, 2017), other mammals (Rizzo et al, 2019), and even the model nematode Caenorhabditis elegans (Toraason et al, 2022) have demonstrated that variables relating to the maternal germline, and in particular oocyte age, may increase the probability of nondisjunction during meiosis. The current evidence, while mostly limited to humans and domesticated mammals, suggests that chromosomal aberrations and their impacts on tness may be prevalent across taxa, and may be predisposed by genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 94%